Banano (cavendish gigante) de rechazo como sustitución parcial de cebada en la calidad fisicoquímica y sensorial de la cerveza artesanal - Tirado Vera, Jhon Washington (2018)
The objective of the research was to evaluate the physicochemical and sensory effects of partial substitutions of barley with rejection bananas in obtaining of type craft of beer as an alternative for its use. The behavior of the factor under study was determined: percentage of banana, in relation to the content of the mixture of malted barley mix (95% pilsen malt + 5% caramel malt), which originated three treatments; T1 (25% banana + 75% mixture of malted barley), T2 (50% banana + 50% mixture of malted barley), and T3 (75% banana 25% mixture of malted barley), together a control was elaborated (100% mixture of malted barley).The physicochemical variables (pH, total acidity, density and alcohol grade) were evaluated by applying a one-way ANOVA and Dunnet test. The organoleptic characteristics (color, smell and flavor) were evaluated with a panel of untrained judges and by means of the Friedman test. All the treatments complied with what was established by the NTE INEN 2262, resulting in a better treatment for the T1 that obtained 4.49 pH, 0.25% total acidity, and 5.78% alcohol established by the norm, the density obtained an average of 1.025 g/ml. In the results of the treatments against the control there were no significant difference in the parameter of pH and total acidity, while the density of T1 has a significant difference, like the percentage of alcohol in the three treatments. In the sensory analysis, T3 was the best for the color attribute, and T1 for smell and taste.